"Religion" and the Human Thing. (2nd October 2021) - Heilke, Thomas
Abstract: Paleolithic cosmos-dwellers likely understood their environment in an integrated fashion–the realm of the gods and the realm of everyday life were not two separate spheres of activity. Religion has been abstracted in modern thought into a set of beliefs, practices, or activities that reside "outside" of or aside from the natural world in which human beings live. This abstraction makes it difficult to fully imagine how pre-modern humans conceived of existence in a cosmos. Thucydides provides interesting insights into how one can "bracket" religious beliefs and practices, yet continue to recognize the integration of religion into quotidian human affairs.